Prevalence and associated factors of distress and coping strategies among school-going late adolescents in Kilinochchi South Educational Zone - Arumainathan, N.C.; Saravanabavan, N.; Coonghe, P.A.D. (University of Jaffna, 2024)
Background and objective: Distress significantly impacts the daily lives of adolescents by disrupting their working capacity, academic performance, and contributing to comorbidity. The development of distress is associated with various day-to-day life factors and can lead to harmful consequences. The aim of this study was to determine the prevalence and associated factors of distress and coping strategies among school-going late adolescents (Grade 12 and 13) in Kilinochchi South Education Zone. Method: A descriptive cross-sectional study was conducted among 593 adolescents aged between 17 to 19 years, using multi-stage probability proportionate cluster sampling. Data were collected using a self-administered questionnaire, which included the Kessler Psychological Distress Scale (K10), the Modified Scale of Coping Inventory for Stressful Situations (CISS), and questions to evaluate associated factors. The relationship between distress and associated factors, as well as coping strategies, was assessed by the chi-square test and independent sample t-test. A p value ≤ 0.05 was considered significant. Results: The study sample comprised 230 (38.8%) males and 363 (61.2%) females. The prevalence of psychological distress among the participants was 33.1% (n=196; 95% CI 29.3- 37.0). Psychological distress was significantly associated with being female (p=0.012), having a single parent family without a father (p=0.008), father’s employment (p=0.022), mother’s employment (p=0.037), living conditions (p=0.025), parents suffering from chronic illnesses (p=0.022), achieving lower than expected marks in the last examination (p<0.001), participating in extracurricular activities (p=0.003), perceiving teachers as not helpful (p<0.001), experiencing favoritism from teachers (p<0.001), and having a history of alcohol consumption (p=0.024). In the sample, 445 (75%) had high skills in coping and 148 (25%) had medium skills in coping. There were no students with low skills in coping. The majority of distressed students (84.2%) had high skills in coping while 11.8% of distressed students had medium skills in coping (p<0.001). Conclusion: A substantial proportion adolescents had distress. Contributors to distress include female gender, parental factors and academic burden. Level of coping skills was high but varied with distress level.
Keywords: Psychological distress; Adolescents; Coping strategies; Kilinochchi